Application of the Rule of Law to Support the Administration of Thai Monastic Affairs - Phradhammavachirajahn; Phrapanyarattanakorn; Phramongkolsutakam; Phrakrusivachiranurak (Mahachula Academic Journal, 2025)
The objectives of this research paper are 1) to study the concepts, theories and principles of the rule of law for the administration of monastic affairs in accordance with the law of the monastic community, 2) to study the application of the rule of law in supporting the administration of monastic affairs, and 3) to propose a model of management of monastic affairs in accordance with the law of the monastic community in the rule of law of the Thai monastic community. The results of the research show that the rule of law in Buddhism consists of 8 important Buddhist principles: Sovereignty 3, Prejudice 4, Brahma Vihara 4, Influence 4, Sangkha 4, Saraniyadhamma 6, Sappurisdharma 7 and Apriha Niyadhamma 7, which can be effectively applied to the management of monastic affairs in 6 areas: administration, religious education, education, welfare, mission, public utilities, and public work. The research has presented a model of monastic affairs management called "6D+3C", where 6D refers to the 6 missions that are driven by the rule of law, and the 3Cs are supporting factors, namely competency, compatibility, and corruption prevention, which are new knowledge that can be used to develop the administrative system of the monastic community to be transparent, fair, and in line with the Dharma Discipline with the times.